Development of web-based engineering numerical software (WENS) using MATLAB: Applications to linear algebra - Kim, Albert S.; Park, Chanho; Park, Si-Hwan (Computer applications in engineering education, 2003)
In this article, we present Web‐based Engineering Numerical Software (WENS) developed using MATLAB and its Web Server Toolbox (WST) in order to provide basic solution tools in linear algebra, including eigenvalue problems, which are extensively used in engineering applications and education. © 2003 Wiley Periodicals, Inc. Comput Appl Eng Educ 11: 67–74, 2003; Published online in Wiley InterScience (www.interscience.wiley.com); DOI 10.1002/cae.10038